2012
DOI: 10.1073/pnas.1116727109
|View full text |Cite
|
Sign up to set email alerts
|

Role of prefrontal cortex and the midbrain dopamine system in working memory updating

Abstract: Humans are adept at switching between goal-directed behaviors quickly and effectively. The prefrontal cortex (PFC) is thought to play a critical role by encoding, updating, and maintaining internal representations of task context in working memory. It has also been hypothesized that the encoding of context representations in PFC is regulated by phasic dopamine gating signals. Here we use multimodal methods to test these hypotheses. First we used functional MRI (fMRI) to identify regions of PFC associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(178 citation statements)
references
References 74 publications
13
154
0
3
Order By: Relevance
“…However, it has been argued that it is only through interactions with the basal ganglia that the prefrontal cortex realizes this gating function (O'Reilly 2006), such that the striatum provides gating signals to the frontal cortex (Go/update or NoGo/ maintain) via interactions with the thalamus and the substantia nigra. In support of this model, fMRI studies have observed striatal activity during working-memory tasks that involve updating (Lewis et al 2004;Dahlin et al 2008), and high-resolution fMRI of the midbrain revealed activation in or near the substantia nigra (D'Ardenne et al 2012). Relatedly, frontostriatal interactions have also been implicated in the control of access to workingmemory storage (McNab and Klingberg 2008), which may contribute to interindividual differences in working memory.…”
Section: A Subcortical Dopaminergic Updating Systemmentioning
confidence: 82%
See 1 more Smart Citation
“…However, it has been argued that it is only through interactions with the basal ganglia that the prefrontal cortex realizes this gating function (O'Reilly 2006), such that the striatum provides gating signals to the frontal cortex (Go/update or NoGo/ maintain) via interactions with the thalamus and the substantia nigra. In support of this model, fMRI studies have observed striatal activity during working-memory tasks that involve updating (Lewis et al 2004;Dahlin et al 2008), and high-resolution fMRI of the midbrain revealed activation in or near the substantia nigra (D'Ardenne et al 2012). Relatedly, frontostriatal interactions have also been implicated in the control of access to workingmemory storage (McNab and Klingberg 2008), which may contribute to interindividual differences in working memory.…”
Section: A Subcortical Dopaminergic Updating Systemmentioning
confidence: 82%
“…Fuster 2013). By affecting updating of task-context representations (D'Ardenne et al 2012) and by driving associative reinforcement-learning mechanisms (Schultz 1998), dopamine also plays a key role in this context. A dual role for dopamine in gating and learning opens up for a self-organizing system that learns when to update goals and contexts to maximize rewards and minimize punishments (cf.…”
Section: Maintaining and Realizing Intentionsmentioning
confidence: 99%
“…Guided by these observations, the rationale that treatment-resistant individuals would differ from non-refractory patients in these brain substrates that track clinical improvement, and the idea that treatmentresistant individuals would exhibit striatal FC abnormalities indicative of their specific cognitive and behavioral impairments, we addressed two principal hypotheses. First, treatment-resistant individuals with schizophrenia would display reduced connectivity along nigrostriatal pathways compared with non-refractory individuals, as learning and its influence on action can be impaired in treatment-resistant individuals (Dratcu et al, 2007;Kolakowska et al, 1985), and related processes are regulated by striatum and substantia nigra (Braver et al, 1999a;Braver and Cohen, 1999b;D'Ardenne et al, 2012). Second, frontostriatal disruptions observed when comparing patients with healthy individuals (Quide et al, 2013;Sarpal et al, 2015) would differ as a function of treatment resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which the brain achieves an adaptive balance between flexibility and stability remain the basis of much current investigation in cognitive neuroscience. In PNAS, D'Ardenne et al (1) provide evidence for two key pieces to this puzzle. They demonstrate that the dorsolateral prefrontal cortex (DLPFC) is necessary for flexible updating of contexts to control behavior and that activity in cells of the dopaminergic midbrain may signal an updating response.…”
mentioning
confidence: 99%